Implementation of Digital Flipchart (LEBAD) in Reproductive Health Education for Adolescents with Disabilities - Rahma Trisnaningsih; Ismi Nur Khasanah; Lutfi Annarahayu; Saumi Fijriyah; Mizan Prihastuti; Siti Mahmudah (Indonesian Journal of Global Health Research, 2025)
Adolescents with disabilities face limited access to reproductive health education due to communication barriers, insufficient inclusive learning materials, and a lack of confidence among educators and health workers in addressing sensitive topics. The Digital Flipchart (LEBAD) was developed as an innovative educational medium to support inclusive reproductive health education through accessible digital content tailored for diverse disability groups. This study aimed to describe the implementation and perceptions of teachers and health workers toward the Digital Flipchart (LEBAD) as a medium for reproductive health education among adolescents with disabilities in Bantul District, Yogyakarta. A descriptive qualitative design was employed. The study was conducted from January to August 2025 across 20 special schools (SLB) and several community health centers. Forty participants—comprising SLB teachers and community health workers—were recruited using purposive sampling with maximum variation technique, ensuring representation from different types of disabilities, educational levels, and institutional backgrounds. Data were collected through in-depth interviews, participatory observation, and written feedback. Thematic analysis followed Miles and Huberman’s framework, with validation conducted through triangulation, member checking, and peer debriefing. The findings revealed several main themes: (1) LEBAD as a relevant and beneficial innovation—teachers and health workers found it attractive, easy to use, and contextually appropriate; (2) Improved educator capacity and confidence—participants reported greater ease and readiness in teaching reproductive health; (3) Technical and logistical aspects—some noted environmental and scheduling constraints; (4) Need for content and accessibility development—participants recommended adding more interactive and disability-specific features; and (5) Sustainability and collaboration—both groups emphasised the importance of continuing the program through cross-sector partnerships between schools and health facilities. LEBAD was reported to increase students’ understanding of puberty, personal hygiene, and self-protection, while empowering teachers and health workers to deliver inclusive and engaging reproductive health education. The Digital Flipchart (LEBAD) is an effective, educational, and inclusive innovation that strengthens reproductive health literacy among adolescents with disabilities and enhances the competence of educators and health workers. Sustainable implementation requires continued training, content adaptation for various disabilities, and institutional collaboration between the education and health sectors.